Association between PTGER4 polymorphisms and inflammatory bowel disease risk in Caucasian: A meta-analysis. Issue 34 (21st August 2020) - Wu, Peng-Bo; Qian, Rao; Hong, Chai; Guo, Yi-tian; Yu, Yuan-jie; Zhang, Guo; Tan, Shi-Yun
Abstract: Background: The results from previous studies on association between prostaglandin E receptor 4 (PTGER4) polymorphisms and inflammatory bowel disease (IBD) risk in Caucasian were conflict. The present study aimed to investigate the genetic association by conducting a meta-analysis. Methods: Systematic literature search was conducted through Wiley Online Library, Chinese National Knowledge Infrastructure (CNKI), and PubMed databases. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to investigate the associations between rs4613763 T/C, 17234657T/G polymorphisms, and IBD risk in Caucasian. Results: Twenty case-control studies consisting of 18, 495 Crohn disease (CD) patients and 4203 ulcerative colitis (UC) patients, as well as 26, 063 controls were included in this meta-analysis. The rs4613763T/C polymorphism had obvious influence on CD, UC risk in Caucasian. However, rs17234657T/G polymorphism had obvious influence on CD but not UC in Caucasian. Conclusion: This meta-analysis suggested that both the rs4613763 T/C, rs17234657T/G polymorphisms had obvious influence on risk of CD in Caucasian. In addition, rs4613763 T/C, polymorphism had obvious influence on risk of UC in Caucasian.